Enhanced Adsorption Capacity of Zeolite through Intercalation with Calcium Carbonate of Batissa Violacea Celebensis Shell Waste for Removing Detergent Waste - W. O. Haerunnisah; R. Suhardiman; Wahyu; L. O. Ahmad (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2024)
Zeolites possess pores or layers that can be filled with other molecules, thereby enhancing their acidity, thermal capacity, and surface tension. This, in turn, improves their efficacy in adsorbing organic waste. The main objective of this study is to investigate the material characteristics of ZAA-CaCO3 and its performance in adsorbing detergent waste. The research encompasses several stages, including the preparation of the shell of Biavalvia violacea celebensis waste, natural zeolite preparation, the intercalation process, material characterization, and measurement of adsorption capacity. XRD diffraction analysis revealed that the highest intensity of CaCO3 was observed at angles of 2Ө: 29.4o, 37.4o, and 51.9o. The results of infrared spectroscopy analysis indicated that the chemical activation spectra of ZAA-CaCO3 and ZAA-CaCO3 with a 300oC calcination were similar, except for absorptions at wave numbers 1386 cm-1, 1417 cm-1, 1635 cm-1, 1997 cm-1, and 2359 cm-1, which indicated the presence of carbonate groups of calcium carbonate. Furthermore, morphological analysis using SEM revealed a significant difference between Zeolite Nature, Zeolite Natural Active, and ZAA-CaCO3. The highest percentage of adsorption was observed with ZAA-CaCO3 material at a ratio of 2:1 and a contact time of 120 minutes, resulting in an adsorption capacity of 89.67%.